Associations between strain, herd size, age at first calving, culling reason and lifetime performance characteristics in Holstein-Friesian cows. (13th July 2016) - Adamczyk, K.; Makulska, J.; Jagusiak, W.; Węglarz, A.
Abstract : Cow longevity and lifetime performance traits are good indicators of breeding effectiveness and animal welfare. They are also interrelated with the economics of dairy herd. Unfortunately, a high milk yield is often associated with deteriorated cow health and fertility and, consequently, with an increased culling rate. This situation, observed also in the Polish population of Holstein-Friesian cattle, inspired us to undertake a study on the associations between some factors and lifetime performance characteristics. The data set consisted of the records on 135 496 cows, including 131 526 of the Black and White strain (BW), and 3970 of the Red and White strain (RW) covered by performance recording and culled in 2012. It was found that cows of the BW strain and those from the largest herds (>100 cows) reached higher lifetime and mean daily energy-corrected milk (ECM) yields than cows of the RW strain and those from smaller herds culled at a similar age. Cows youngest at first calving (<2.0 years) were characterised by the highest lifetime ECM yield. It indicates that heifers can be bred even when they are younger than 15 to 16 months with no significant negative effect on their later performance. Infertility and reproduction problems (39.6%) and udder diseases (15.5%) constituted the most frequent reasons for cow culling. Cow longevity and lifetime productivity were considerably affected by the interactions between the studied factors.